Smartphone use as a mediator of self-control and emotional dysregulation in nomophobia: A cross-national study of Indonesia and Malaysia - Safaria, Triantoro; Abdul Wahab, Muhammad Nubli; Suyono, Hadi; Hartanto, Dody (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2024)
Nomophobia has become a worrying phenomenon among young people. Therefore, research is needed to understand this condition more deeply. This study explores cross-cultural differences in nomophobia, emotional dysregulation, self-control, and smartphone use among a sample of university students in Yogyakarta, Indonesia, and Pahang, Malaysia. In addition, it examines smartphone use as a mediator of the effects of emotional dysregulation and self-control on nomophobia. Currently, only a limited amount of research tests explicitly the nomophobia-mediated model across different countries. This study used a cross-sectional design that involved university students from Yogyakarta and Pahang, comprising 215 students from Yogyakarta and 211 from Pahang, resulting in 426 participants. Among these, 110 (25.8%) were female and 316 (74.2%) male, with an average age of 18 (SD = 3.4), who were recruited using purposive sampling. Manova and regression analyses were conducted to examine the hypotheses, with an initial assessment of data normality, multicollinearity, and homogeneity assumptions performed before the analysis. Data were collected using scales for nomophobia, emotional dysregulation, self-control, and smartphone use. The study results indicate that students from Pahang exhibit higher levels of smartphone use and nomophobia compared to those from Yogyakarta (mean: 37.03 vs. 52.137; F = 151.19, p = .000). Emotional dysregulation and smartphone use consistently demonstrate a significant positive role in nomophobia across national contexts (β = 0.191, p = 0.002), (β = -0.414, p = 0.000). At the same time, self-control does not have a significant direct influence on nomophobia. The findings indicate the significant role of emotional dysregulation and smartphone use in nomophobia, the management of which will have implications for mitigating nomophobia.